Emergent cell migration from cell shape deformations and T1 transitions - Harish P. Jain; Richard D. J. G. Ho; Luiza Angheluta (Physical Review Research)
T1 transitions—cell neighbor exchanges—are key drivers of tissue remodeling and fluidization in epithelial monolayers. Using a multiphase field (MPF) model that accounts for dynamic cell shapes, alongside an active elastic solid model lacking cell shape degrees of freedom, we study the spatiotemporal organization of T1 transitions. While individual T1 transitions occur as a Poisson process in time, their spatial distribution is strongly influenced by local cell shape deformations. We identify a dual mechanical response: cells losing neighbors tend to relax their shape isotropically, whereas cells gaining neighbors undergo anisotropic elongation. By analyzing successive T1 events in the MPF model, we find asymmetric spatial patterns that depend on whether a cell gains or loses neighbors. These asymmetries lead to persistent, localized directional motion, even in the absence of external cues. Our results suggest an intrinsic mechanism for directed cell migration driven by local topological rearrangements mediated by cell shape dynamics—a process potentially relevant for epithelial flows during development, morphogenesis, and wound healing.